Analysis of Related Factors of Mother-to-Child Transmission of AIDS and Evaluation of Measures to Prevent Mother-to-Child Transmission. (5th January 2022) - Liu, Yuhuan; Zhang, Yulan; Pang, Lin
Abstract : AIDS is still a major public health facing the world. With the implementation of AIDS prevention projects and the continuous maturity of technology, more and more HIV-positive women choose to have children. However, the children born to these women are a special group. Exposure to HIV and antiviral drugs during the fetal period can increase the success rate of children's elimination of the mother, which is worthy of attention and research. This article focuses on the analysis of the related factors of mother-to-child transmission of AIDS and the evaluation of mother-to-child blocking measures, using the method of field research to conduct experiments on AIDS patients in this city who are pregnant and provide them with antidrug treatment and some barrier measures. Then, the mother-to-child transmission rate was recorded, and the experimental results showed that the antidrug treatment plan is related to mother-to-child transmission. After antidrug treatment, the transmission rate of single-drug treatment is reduced by 5%, and the transmission rate of combined drug treatment is reduced by 10%. It can be seen from this that antidrug treatment is an effective measure to block mothers and babies.